2021
DOI: 10.3390/ijerph18179309
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Knowledge Structure and Trends of Outreach in Public Health Care: A Text Network Analysis and Topic Modeling

Abstract: Outreach programs are considered a key strategy for providing services to underserved populations and play a central role in delivering health-care services. To address this challenge, knowledge relevant to global health outreach programs has recently been expanded. The aims of this study were to analyze the knowledge structure and understand the trends in aspects over time and across regions using text network analysis with NetMiner 4.0. Data analysis by frequency, time and region showed that the central keyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This research used NetMiner4.4.3 (Cyram Inc., Seongnam, Republic of Korea), a software tool used for network analysis and visualization. Along with UCINET and Pajek, NetMiner is a representative tool for social network analysis [35]. A research model was designed for this study, as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…This research used NetMiner4.4.3 (Cyram Inc., Seongnam, Republic of Korea), a software tool used for network analysis and visualization. Along with UCINET and Pajek, NetMiner is a representative tool for social network analysis [35]. A research model was designed for this study, as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Crowdfunding from the perspective of young people Journal of Accounting and Investment, 2024 | 174 indirectly shows the factors that attract the most attention from a problem or topic context. Thus, the SNA approach can be used to describe the structure of knowledge related to the appeal of crowdfunding (Park & Park, 2021). Lynn et al (2020) also used SNA to understand effective crowdfunding campaign patterns on Twitter.…”
Section: Hariwibowomentioning
confidence: 99%
“…Text analysis is based on SNA aimed at analyzing and understanding the dominant topic of text material in big data (Park & Park, 2021). Network theory, which forms the basis of the SNA approach, explains that everything interrelated can be explained in a network (Wichmann & Kaufmann, 2016).…”
Section: Text Analysis and Social Network Analysis (Sna) In Crowdfundingmentioning
confidence: 99%
See 2 more Smart Citations